Masculinity at work : employment discrimination through a different lens - McGinley, Ann C. (New York : New York University Press, 2017)
In late October 2013, the Miami Dolphins' player Jonathan Martin walked out on his team and checked into a mental health institution. The original story implied that Martin could not take the professional pressure. Within days, the story changed. News sources reported that Martin's teammates had repeatedly bullied him and as a result, the 24 year-old African American player suffered serious depression. The response was skeptical, and many opined the harassment involved was simply locker room banter that all players endure; essentially, that boys will be boys. 'Masculinity at Work' uses the Jonathan Martin case and others to analyse Title VII of the Civil Rights Act of 1964 through the lens of masculinities theory.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 5, 2016).
Keywords: Discrimination in employment -- Law and legislation -- United States; Masculinity -- Social aspects -- United States; Sexual harassment -- Law and legislation -- United States; Sex role in the work environment -- United States; Law; United States of America, USA; Law & society, gender issues; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general; Employment & labour law: general